2015
DOI: 10.1212/wnl.0000000000001867
|View full text |Cite
|
Sign up to set email alerts
|

Education Research: Changing medical student perceptions of dementia

Abstract: Background: Medical students' comfort level working with dementia is poorly understood, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
(9 reference statements)
2
17
0
Order By: Relevance
“…148). The students' access to their own emotions during the art experiences in our study may relate to the literature supporting the use of art to build empathy in health care provider education (Casey, 2009;Cassel, 1976;Charon, 2010;Fraser & al Sayah, 2011;Gaufberg & Williams, 2011;George, Yang, Stuckey, & Whitehead, 2012;Peloquin, 1996a;Perry et al, 2011;Roberts & Noble, 2015;Schaff et al, 2011).…”
Section: Pre and Postmodule Survey Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…148). The students' access to their own emotions during the art experiences in our study may relate to the literature supporting the use of art to build empathy in health care provider education (Casey, 2009;Cassel, 1976;Charon, 2010;Fraser & al Sayah, 2011;Gaufberg & Williams, 2011;George, Yang, Stuckey, & Whitehead, 2012;Peloquin, 1996a;Perry et al, 2011;Roberts & Noble, 2015;Schaff et al, 2011).…”
Section: Pre and Postmodule Survey Resultsmentioning
confidence: 67%
“…For example, visual arts in professional education is used to develop clinical skills, including observation skills, critical thinking, perspective taking, and rapport building (Casey, 2009;Cassel, 1976;Charon, 2010;Gaufberg & Williams, 2011;Ousager & Johannessen, 2010;Schaff, Isken, & Tager, 2011). This interest was spurred by studies indicating a decline in medical students' empathy during medical school (Hojat et al, 2009;Roberts & Noble, 2015). It has been suggested that learning through medical humanities improves patient care, as well as self-understanding and stress relief for physicians in training (Gaufberg & Williams, 2011;Hammer et al, 2011;Ousager & Johannessen, 2010;Perry, Maffulli, Willson, & Morrissey, 2011;Roberts & Noble, 2015).…”
Section: An Important Backdrop For Exploring Art Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the “A Friend for Rachel” programme that was developed recently, undergraduate students help people in early‐stage dementia to continue to enjoy their interests, remain active, develop new relationships and avoid isolation . The humanistic approach developed by these non‐clinical art‐centred programmes should be prioritised in future patient care …”
Section: Discussionmentioning
confidence: 99%
“…The students collaborate directly with U-M Silver Club Mild Memory Loss Program club members on art, music, dance, or writing projects that they design and create together once a week for 90-minutes throughout the course of a semester. Supporting our program goals, research has shown that medical students who participated in one 90-minute museum-based, art-centered program for persons with dementia and their family caregivers gained increased comfort and new insights into how arts programming can improve quality of relationships [9].…”
mentioning
confidence: 95%